ROLE OF KNOWLEDGE SHARING AND LEADERSHIP STYLE IN IMPROVING EMPLOYEE PERFORMANCE WITH WORK CULTURE AS AN INTERVENING VARIABLE - Sanosra, Abadi; Hakim, Arief Rahman; Cahyono, Dwi; Qomariah, Nurul; Thamrin, Muhammad (Universitas Brawijaya, Indonesia, 2022)
Competition in the cement industry is increasing with the opening of opportunities for foreign cement industries to take part in the country. This paper aims to re-examine the effect of sharing and leadership skills on work culture. The next research aims to know the effect of knowledge sharing and leadership style on employee performance. This research was conducted at PT. Semen Bosowa, which is located in Banyuwangi Regency. The number of employees owned by PT. Semen Bosowa, located in Banyuwangi, has 94 employees, all used as research samples (saturated samples). Descriptive analysis is used to describe respondents and variables in the study. The study used test tools to test the validity of research data and the reliability of research data to measure the questionnaire. PLS (Partial Least Square) analysis with the Smart PLS version 3 application was used to test the research hypotheses of 5 (five) direct hypotheses and two indirect hypotheses. The research results after the analysis is that knowledge sharing in PT. Semen Bosowa has no impact on the work culture of the employees. The leadership style in the organization has a positive impact on the work culture in the PT. Bosowa Banyuwangi. Knowledge sharing of employees of PT. Semen Bosowa turned out to be able to improve employee performance. The leadership style that exists at PT. Bosowa Banyuwangi has a positive and significant effect on employee performance. The next result is the work culture of the employees of PT. Bosowa Banyuwangi has no effect on employee performance.